Analysis of the availability of bronchodilators listed in the medical insurance catalog for treatment of chronic obstructive pulmonary disease in community health service centers in Shanghai - DENG Hui; YANG Qundi; WU Han; LIU Danni; LA Xuena; ZHENG Yang; SHI Yan (Shanghai yufang yixue)
ObjectiveTo assess the availability of bronchodilators for treatment of chronic obstructive pulmonary disease (COPD) in community health service centers (CHCs) in Shanghai.MethodsOn the basis of previous research, the questionnaire was updated, and surveys were conducted from April to May 2023 in CHCs in Shanghai, with a focus on the availability of medications for COPD treatment. According to the National Basic Medical Insurance, Work Injury Insurance, and Maternity Insurance Drug List (2023 Edition), a total of 24 types of bronchodilators for COPD treatment were identified. The availability rates were used to assess the accessibility of specific drugs in CHCs, and the dispensing rates were used to evaluate the variety of these medications in CHCs.ResultsA total of 248 CHCs responded, with a response rate of 100.0%. Among them, a total of 232 CHCs (93.5%) were equipped with bronchodilators. In terms of availability rates, the availability rates for β2 adrenoreceptor agonists, muscarinic antagonists, combination drugs, and xanthines drugs were 86.3%, 52.0%, 52.4%, and 85.1%, respectively. Regional differences were observed, in that salbutamol/levalbuterol and budesonide-formoterol were less available in suburban CHCs, ipratropium bromide had lower availability in urban CHCs, and aminophylline was more available in suburban CHCs. Regarding the dispensing rates of the 24 types of bronchodilators for COPD treatment, the median of types equipped by CHCs was 5, with a total of 200 CHCs (80.6%) equipped with fewer than 7 types of bronchodilator drugs.ConclusionThe proportion of CHCs in Shanghai equipped with bronchodilators for COPD is relatively high. However, there exist problems such as limited variety of stocked medications, significant differences in the availability of different drugs, and regional imbalances in drug stocking. To improve the standardized diagnosis, treatment, and management of COPD patients, it is recommended to enhance the availability of COPD treatment medications in CHCs.